Current Conveyor All-Pass Sections: Brief Review and Novel Solution - Sudhanshu Maheshwari (The Scientific World Journal)
This study relates to the review of an important analog electronic function in form of all-pass filter’s realization using assorted current conveyor types and their relative performances, which resulted in a novel solution based on a new proposed active element. The study encompasses notable proposals during last the decade or more, and provides a platform for a broader future survey on the topic for enhancing the knowledge penetration amongst the researchers in the specified field. A new active element named EXCCII (Extra-X second generation current conveyor) with buffered output is found in the study along with its use in a new first-order all-pass section, with possible realization using commercially available IC (AD-844) and results.